Educational handbook for healthcare professionals: Preventing complications and treating peristomal skin - Salomé,Geraldo Magela (2019)
Abstract Objective To create and validate a handbook for the prevention of peristomal skin complications. Methods For the elaboration of the handbook, a literature review was conducted in the following databases: Cochrane Library, SciELO, LILACS, and MEDLINE. The handbook “Preventing and treating the complications of intestinal peristomal skin” was elaborated in nine steps. The first step addressed the concepts of ostomy, stoma type, and ostomy classification. In the second step, the following were described: definition of the collection equipment, type of collection equipment, and technique of changing one- and two-piece equipment. In the third step, the peristomal skin cleansing technique was described. In the fourth step, the types of complications of the peristomal skin were listed. In the fifth step, preventive approaches to avoid complications with the peristomal skin were described. In the sixth step, the therapeutic approaches in the treatment of aforementioned peristomal skin complications were addressed. In the seventh step, the handbook layout was created by an Information Technology professional. In the eighth step, the handbook was validated by 25 nurses. In the ninth step, the final version of the instrument was laid out. Results The final version of the “Preventing and treating the complications of intestinal peristomal skin” handbook has 37 pages. It was registered in the International Standard Book Number: 978-85-67647-46-3, standard format size (21 cm high by 15 cm wide), totaling 50 illustrations. In the first evaluation, the evaluators assessed the manual as partially adequate to completely adequate. In the first evaluation, the content validity index ranged between 0.88 to 1.0; no 100% agreement was observed among the evaluators' answers. In the second evaluation, as an agreement was observed in all items, the content validity index was 1.0. Conclusion The handbook “Preventing and treating the complications of intestinal peristomal skin” was elaborated based on scientific principles and had its content, language, and design validated by specialists in the field.